Disease Activity, Inflammation Markers, and Quality of Life Are Associated with Muscle Strength in Croatian Rheumatoid Arthritis Patients—A National-Based Study - Mislav Radić; Ivan Vlak; Marijana Vučković; Senka Rendulić Slivar; Mira Kadojić; Doris Stamenković; Dubravka Bobek; Josipa Radić; Andrea Gelemanović; Andrej Belančić; Erim Bešić; Tonko Vlak (Medicina)
Background and Objectives: Rheumatoid arthritis (RA) patients experience sarcopenia and decreased muscle mass and handgrip strength, leading to decreased quality of life and disability. The prevalence of RA varies across regions. This study aimed to evaluate the factors associated with RA in Croatian regional centres and explore correlations between clinical parameters and muscle strength. Materials and Methods: Included in this study were 267 stable RA patients from four Croatian clinical centres. The patients’ mean age was 60.4 ± 12.0 years, with 12.7% of them being male. For each study participant, information was gathered on their anthropometric characteristics, clinical and laboratory indicators, quality of life, disease activity, and sociodemographics. Results: The main results showed that in the female RA participants, the significant positive predictors are weight, height, exercise, VAS, and haemoglobin level. The negative predictors are the use of conventional synthetic disease-modifying anti-rheumatic drugs, the use of biological disease-modifying anti-rheumatic drugs, the number of tender joints, the number of swollen joints, the estimated sedimentation rate, the C-reactive protein, the disease activity score, the parameters of the EQ5D, and being prescribed with three or more medications. In the male RA participants, significant predictors of muscle strength are only weight, height, and anxiety/depression difficulties, according to the EQ5D. Conclusions: This study showed correlations between muscle strength and the parameters of disease activity, inflammation parameters, health-related quality of life, therapy, and exercise in the female RA participants in Croatia.